2016
DOI: 10.1371/journal.pone.0167525
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex Sensitivity Predicts Short-Term Outcome of Postural Tachycardia Syndrome in Children

Abstract: ObjectiveThe study was designed to examine if baroreflex sensitivity (BRS) could predict the short-term outcome of postural tachycardia syndrome (POTS) in children.MethodsSeventy-seven children subjects were included in the study. Among them, 45 children were in the POTS group and another 32 healthy children were in the control group. A ninety-day clinical follow-up was conducted and the symptom score before and after the follow-up was calculated for POTS patients by using POTS score system. Hemodynamics and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Muenter Swift et al reported that POTS patients had exaggerated muscle sympathetic nerve activity (MSNA) responses to baroreflex challenges (including vasoactive drug boluses, Valsalva maneuvers and the standing-up test) compared to healthy control subjects (15). Li et al also found that BRS in children with POTS was significantly higher than that in healthy children (18.76 ± 9.96 ms/mmHg vs. 10 ± 5.42 ms/mmHg, P < 0.01) (14). BRS was positively correlated with HR changes in the POTS group ( r = 0.304, P < 0.05), indicating that BRS was related to the severity of POTS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Muenter Swift et al reported that POTS patients had exaggerated muscle sympathetic nerve activity (MSNA) responses to baroreflex challenges (including vasoactive drug boluses, Valsalva maneuvers and the standing-up test) compared to healthy control subjects (15). Li et al also found that BRS in children with POTS was significantly higher than that in healthy children (18.76 ± 9.96 ms/mmHg vs. 10 ± 5.42 ms/mmHg, P < 0.01) (14). BRS was positively correlated with HR changes in the POTS group ( r = 0.304, P < 0.05), indicating that BRS was related to the severity of POTS.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that POTS may be related to autonomic nerve dysfunction, hypovolemia, decreased skeletal muscle pump activity and injured vascular endothelium demonstrated by flow-mediated vasodilation (FMD) and midregional pro-adrenomedullin (MR-proADM) (713). Autonomic nerve dysfunction plays an important role in the induction of this disease, and the increased baroreflex sensitivity (BRS) is the key factor (14, 15). BRS has been associated with the severity of POTS and could be used as an effective index to predict the short-term outcome of POTS in children (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms of PoTS include nausea, headache, palpitations, dizziness, chest discomfort, blurred vision, shortness of breath, and, in severe cases, syncope. The etiology of PoTS remains quite unclear; some authors suggest that this syndrome is mainly induced by an autonomic nerve dysfunction, and in particular by an increased baroreflex sensitivity (BRS), and BRS is correlated with PoTS symptoms [95,96]. Some studies on hypertensive patients have shown a relationship between HHcy levels and increased BRS [97], probably due to the regulation of oxidative stress mediated by Hcy.…”
Section: Hhcy and Cardiovascular Diseasesmentioning
confidence: 99%
“…The reported therapeutic effects in children with NMS have varied. Therefore, some indicators for predicting the therapeutic response have been studied including baroreflex sensitivity,[ 8 ] the heart rate corrected QTd,[ 9 ] the body mass index, plasma CNP[ 10 ] and so on. These studies provide individualizing therapy for syncopal cases and need to be wildly applied in the clinics in the future.…”
Section: A Dvances O Ver the P mentioning
confidence: 99%